Use of Social Media in the Teaching–Learning Process: An Insight from Community Campuses in Chitwan - Sapkota, Tulasi; Kandel, Krishna Prasad (Jana Adarsha Research Journal, 2026)
The proliferation of social media has restructured communication and has provided new opportunities for teaching and learning at the college level. Teachers at the community campuses in Nepal started using social media based applications including Facebook, Messenger, YouTube and WhatsApp along with Google Class Room to carry out teaching and learning activities for delivering lectures online, for sharing reading materials among them, communicating among themselves as well as with students for pedagogical process. Community colleges in Chitwan accommodate students from various socio-economic and academic categories who have encountered both opportunities and challenges while using social media as an instructional tool. This paper aims to assess lecturers’ perspective on the use of social media for teaching and learning in community campuses in Chitwan. Through a qualitative content analysis, five emergent themes were accessibility and connectivity, pedagogical use of social media, socio-economic and digital divides, and future agenda of social media-supported learning. The results indicate that social media has improved the communication, flexibility, and informal learning possibilities while digital divide, distraction and pedagogical preparedness remain as challenges. The research present insights within context and makes recommendations for the relevant use and implementation of social media in higher education in resource poor environments.